Gastroenteropancreatic Neuroendocrine Neoplasms in Patients with Inflammatory Bowel Disease An ECCO CONFER Multicentre Case Series - Festa Stefano; Zerboni Giulia; Derikx Lauranne A. A. P.; Ribaldone Davide Giuseppe; Dragoni Gabriele; Buskens Christianne; Dijkum, van Els Nieveen; Pugliese Daniela; Panzuto Francesco; Krela-Kaźmierczak Iwona; Mintz Hilla Reiss; Shitrit Ariella Bar-Gil; et al. (2022)
Gastroenteropancreatic Neuroendocrine Neoplasms (GEP-NENs) have rarely been reported in association with inflammatory bowel diseases (IBDs).An ECCO COllaborative Network For Exceptionally Rare case reports project (ECCO-CONFER) collecting cases of GEP-NENs diagnosed in patients with IBD.GEP-NEN was diagnosed in 100 IBD patients [61% female, 55% Crohn's disease, median age 48 years (IQR 38-59)]. The most common location was the appendix (39%) followed by the colon (22%).Comprehensive IBD-related data was available for 50 individuals with a median follow-up of 30 months (IQR 11-70) following NEN diagnosis. Median duration of IBD at NEN diagnosis was 84 months (IQR 10-151), and in 18% of cases NEN and IBD were diagnosed concomitantly. At diagnosis, 20/50 were stage-I (T1N0M0), and 28/50 graded G1 (ki67≤2%).Incidental diagnosis of NEN and concomitantly with IBD diagnosis were associated with an earlier NEN stage (p=0.01 and p = 0.02, respectively). Exposure to immunomodulatory or biologic therapy was not associated with advanced NEN stage or grade. Primary GEP-NEN were more frequently found in the segment affected by IBD (62% vs. 38%). At the last follow-up data, 47/50 patients were alive, and only two deaths were related to NEN.In the largest case series to date, prognosis of patients with GEP-NEN and IBD seems favorable. Incidental NEN diagnosis correlates with an earlier NEN stage and IBD-related therapies are probably independent of NEN stage and grade. The association of GEP-NEN location and the segment affected by IBD may suggest a possible role of inflammation in NEN tumourigenesis.
Keywords: Klinikai orvostan